Indians in Minnesota - Graves, Kathy Davis (Book collections on Project MUSE., 2007)
Characterized by a balanced perspective and a comprehensive approach, Indians in Minnesota provides an account of Ojibwe and Dakota Indians living in both reservation and urban settings. Compiled from interviews with tribal members, as well as data from the 2000 Minnesota Census and federal and state reports, the fifth edition of this resource examines the continuing needs of Indians in the twenty-first century.